Fabrication and Characterization of Nanocrystalline Hydroxyapatite Extracted from Bovine Bone at Different Calcination Temperatures - Bano, Nazia; Salwah, Suzi; Basri, Hatijah; Adzila, Sharifah; Shuaib, Nasir (International Journal of Integrated Engineering, 2019)
Hydroxyapatite (HAP) is a calcium phosphate based bioceramics and a basic mineral component of teeth and bones of vertebrates. Its chemical and structural features are analogous to the inorganic components of bone. The present work focuses on the fabrication and characterizations of nanocrystalline HAP extracted from bovine bone at different calcination temperatures (600, 800, and 1000Â°C) without the use of chemicals/solvents. Therefore, it is a green technology. The characterizations of the extracted n-HAP were carried out by X-ray diffraction (XRD), Fourier transforms infrared (FTIR) and Field emission scanning electron microscopy (FESEM)  The FTIR results confirmed the presence of phosphate PO4-3, hydroxyl OH-1 and carbonate CO3-2 groups in the n-HAP powder. FESEM observation confirmed the hexagonal rod like structure. XRD analysis revealed that extracted n-HAP has a hexagonal crystal structure and crystallite size was in the range of 10.48-84.08 nm. Crystallinity degree and crystallite size gradually increased with the intensification of calcination temperature from 600 Â°C -1000 Â°C.